ANALYSIS OF THE POTENTIAL OF THE LEADING ECONOMIC SECTOR OF MAROS DISTRICT - Arsyad, Rahmat; Violin, Vivid (Jurnal Ekonomi Balance, 2021)
The focus of this research is to analyze the potential of the economic sectors in Maros Regency by looking at the role of the sector/industry in the parent region/upper region in this case South Sulawesi Province and to find out changes or shifts in certain sectors in the regional and local economy compared to the economy of the parent region/overlying region in the 2015-2019 period. By using the Location Quotient (LQ) approach and shift-share analysis, the objectives of this study are to find potential economic sectors in Maros Regency and determine the basic economic sector and non-basic economic sector also to determine changes and shifts in certain sectors in the economy. The regional economy of Maros Regency is compared with the wider economy in this case South Sulawesi Province in order to map the focus of sectoral economic development in Maros Regency. The stages in this research include preparation and preparation of proposals, preparation of research instruments, implementation of research, collecting data, then preparing reports and discussing research results. Prepare articles for submission to articles in accredited National Journals ranked 1-6; Intellectual work: Expansion: Journal of Economics, Finance, Banking, and Accounting.